2022
DOI: 10.1128/jvi.01713-21
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Rift Valley Fever Virus RNA-Dependent RNA Polymerase

Abstract: Rift Valley fever virus (RVFV) belongs to the order Bunyavirales and is the type species of genus Phlebovirus , which accounts for over 50% of family Phenuiviridae species. RVFV is mosquito-borne and causes severe diseases in both humans and livestock, and consists of three segments (S, M, L) in the genome. The L segment encodes an RNA-dependent RNA polymerase (RdRp, L protein) that is responsible for facilitating the replication and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Recently, cryo-electron microscopy (cryo-EM) data from single-particle analysis became available describing relevant functional states of Machupo virus (MACV), LACV and LASV L proteins in complex with vRNA, emphasizing how these complex molecular machines undergo major conformational changes during viral genome replication and transcription (13,14,27,28). However, to date, structures of the SFTSV and Rift valley fever virus (RVFV) L proteins, as models for phenuiviruses, are only available in an apo state, i.e., without vRNA (17,(29)(30)(31)(32)(33). These structures demonstrated that the overall architecture of the phenuivirus L protein was similar to the structure of the heterotrimeric influenza virus polymerase complex and the peribunyavirus LACV L protein but also identified some notable differences between bunyavirus and influenza virus polymerases, the most apparent being differences in the fingertip's insertion (SFTSV L protein residues 913 -920).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cryo-electron microscopy (cryo-EM) data from single-particle analysis became available describing relevant functional states of Machupo virus (MACV), LACV and LASV L proteins in complex with vRNA, emphasizing how these complex molecular machines undergo major conformational changes during viral genome replication and transcription (13,14,27,28). However, to date, structures of the SFTSV and Rift valley fever virus (RVFV) L proteins, as models for phenuiviruses, are only available in an apo state, i.e., without vRNA (17,(29)(30)(31)(32)(33). These structures demonstrated that the overall architecture of the phenuivirus L protein was similar to the structure of the heterotrimeric influenza virus polymerase complex and the peribunyavirus LACV L protein but also identified some notable differences between bunyavirus and influenza virus polymerases, the most apparent being differences in the fingertip's insertion (SFTSV L protein residues 913 -920).…”
Section: Introductionmentioning
confidence: 99%
“…Here we focused on those in residues 924, 1050 and 1303 because of their location in the catalytic core of the RNA-dependent RNA polymerase (RdRp). In particular, residue 924 is located within motif F in the RdRp core, a motif involved in the binding of the incoming rNTP ( te Velthuis, 2014 ; Ferron et al., 2017 ; Wang et al., 2021 ) as well as in the interaction of favipiravir with the viral polymerase. A small number of viruses has been isolated with altered sensitivity to favipiravir that share the substitution of a conserved K within the F-motif, associated to a cost to viral fitness that can be restored by accompanying mutations, and these changes affect the polymerase activity and maybe also its fidelity ( Delang et al., 2014 ; Abdelnabi et al., 2017 ; Goldhill et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since G924 is structurally located between the two key positive-charged residues K918 and R926 conserved in F-motifs of RdRps from different RNA-virus families ( te Velthuis, 2014 ; Peng et al., 2021 ), it seemed reasonable to attribute a significant role to the G924S substitution and its combination with I1050V and/or A1303T. The recent cryo-EM model of RVFV RdRp locates residue 924 in the fingertips, residue 1050 within the finger node and 1303 within the thumb ( Wang et al., 2021 ), but no precise locations or interactions nor an obvious structural/physical connection among the three residues provide a clue about their role ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations